Hairy Cell Leukemia: the good news of a bad disease - Mónica Seidi; Guadalupe Benites; Almerindo Rego (Sociedade Galega de Medicina Interna, 2017)
Hairy Cell Leukemia (HCL) is an uncommon chronic B cell Lymphoproliferative disorder characterized by the accumulation of a small mature B cell lymphoid cells with abundant cytoplasm and "hairy" projections within the peripheral blood smear, bone marrow and splenic red pulp. Most patients with HCL present with symptons related to splenomegaly or cytopenias, including some constitucional symptons, however one quarter of them is asymptomatic and is referred due to incidental findings. The authors decided to report a clinical case of hairy cells leukemia in an asymptomatic patient due to the rarity of this neoplasia (2% of all leukemias and less than 1% of limphoids neoplasms) and because it corresponds to the most successfully treatable leukemia.